Toxicity of Trewia nudiflora-mediated silver nanoparticles on mosquito larvae and non-target aquatic fauna. (2nd January 2022) - Esan, Venkattan; Elanchezhiyan, Chakkaravarthy; Mahboob, Shahid; Al-Ghanim, Khalid A.; Al-Misned, Fahad; Ahmed, Zubair; Elumalai, Kuppusamy; Krishnappa, Kaliyamoorthy; Marimuthu, Govindarajan
Abstract: In this study, we synthesized and characterized (UV–vis, XRD, FTIR, SEM, TEM, and AFM) Trewia nudiflora -assisted silver nanoparticles (Tn-AgNPs). The toxicity of T. nudiflora leaf aqueous extract and Tn-AgNPs was tested against Anopheles stephensi, Aedes aegypti, and Culex quinquefasciatus larvae and its LC50 values were 121.82/16.69, 130.51/18.11, and 142.38/19.53 μg mL –1, respectively. Moreover, the biotoxicity was analyzed against the aquatic non-target fauna Anisops bouvieri, Diplonychus indicus, and Gambusia affinis . The LC50 values of non-target fauna were 1064.66–26, 537.05 μg mL –1 . Thus, the Tn -AgNPs significantly controlled the mosquito larvae with less toxic effects on aquatic non-target fauna.